The Influence of SAK EMKM Socialization, Accounting Understanding and Education Level on the Implementation of SAK EMKM (In MSMEs in Cinambo District, Bandung City) - Herdiansyah Gunawan; Deni Hamdani (eCo-Buss, 2024)
Definitely there are several roles played by MSMEs in driving economic growth and development throughout the country. With this being the case, financial reporting and funding challenges often plague these firms. These challenges must be resolved to achieve anything. Financial Accounting standars for micro, smalls and mediums-sized entities primary aim is to make accrual-based financial statements simpler and improve bank borrowing. Despite its benefits, Financial Accounting standars for micro, smalls and mediums-sized entities has not been implemented often, especially in Cinambo District, Bandung City. The inadequate training on how to deal with people, failure to understand business language and general lack of knowledge by small scale business operators are some of the reasons why this is happening. Several studies have found that accounting literacy is a significant determinant for the adoption of Financial Accounting standars for micro, smalls and mediums-sized entities. Objectives are set using research methods to address problems. This study uses quantitative research methodologies: descriptive and verification techniques in analyzing factors affecting the application of Simplified Financial Accounting Standards for Micro, Small, and Medium Entities (Financial Accounting standars for micro, smalls and mediums-sized entities) in Cinambo District, Bandung City, Indonesia. The appraisal of regression analysis involves an assessment of dependability, typicality, hetroscedasticity, the F test and finally the t-test. As shown by two Cronbach’s alpha coefficients of 0.740 and 0.901, a reliability assessment demonstrates that there is satisfactory internal consistency for this measurement instrument. The test for normality indicates that it does exist. Heteroscedasticity shows no trend in the distribution of data sets. The high F value (14.811) and low significance (0.000) of the F test show that the regression model is significant. The t test shows that the variables "Socialisation of Financial Accounting standars for micro, smalls and mediums-sized entities" and "Accounting Understanding" are considerably affecting the variable "Application of Financial Accounting standars for micro, smalls and mediums-sized entities," whereas the variable "Education Level" has a less strong one.